The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China - Ma, Libin; Ma, Ge (Zootaxa, 2019)
Gorochovius furvus sp. n. is the second known species of the genus Gorochovius Xie, Zheng & Li, 2004. The new one is very similar to G. trinervus. But it is distributed farther south than the that species. They can be identified by morphological and acoustical characters. Here, the new species was described, and all species are illustrated and their calling songs analyzed.